The effect of fast application of the tactical training on the kinds of speed and basic skills in football - Radi, Saleh (Journal of Physical Education, 2008)
the problem in football Is the slowly in the performance in the match. Because of the weak in the basic skills and the slowly in the speed. The aim of the study is to know . if the fast performance to the skills and kinds of speed. The conclusions is the fast application of the tactical training Effect on the progresses of the skills and some kinds of the speed.